Predicting quadrupole relaxation enhancement peaks in proton R1-NMRD profiles in solid Bi-aryl compounds from NQR parameters. (18th April 2019) - Gösweiner, Christian; Kruk, Danuta; Umut, Evrim; Masiewicz, Elzbieta; Bödenler, Markus; Scharfetter, Hermann
ABSTRACT: We propose a simple method to calculate and predict quadrupole relaxation enhancement (QRE) features in the spin-lattice nuclear magnetic relaxation dispersion (R 1 -NMRD) profile of protons ( 1 H) in solids. The only requirement is the knowledge of the nuclear quadrupole resonance (NQR) parameters of the quadrupole nuclei in a molecule. These NQR parameters – the quadrupole coupling constantQ c c and the asymmetry parameter η – can be determined by NQR spectroscopy or using quantum chemistry calculations. As there is an increasing interest in using molecules producing high field QRE features as, e.g. for contrast enhancing agents in magnetic resonance imaging, the experimental efforts of seeking for suitable compounds can be reduced by pre-selecting molecules via calculations. Also, the method can be used to extract NQR parameter, and thus structural information, fromR 1 -NMRD profiles showing QRE features. In this article, we describe the calculation procedure and present examples of comparing the result to experimentalR 1 -NMRD data of two different solid 209 Bi-aryl compounds. GRAPHICAL ABSTRACT: